ASTAXANTHIN CONTENT OF GREEN MICROALGAE BOTRYOCOCCUS SP. UNDER SODIUM CHLORIDE SALINITY STRESS - Dzaky Ramadhan, Syamidzar
Astaxanthin is well-known for its natural antioxidant activity. This compound is synthesized by several organisms, such as microalgae. Botryococcus sp. as a green microalgae is capable to accumulate some of high-value carotenoids including astaxanthin even though in low concentration.. Salinity stress can promote astaxanthin production in green microalgae culture. The aim of this research is to determine the astaxanthin content of Botryococcus sp. under sodium chloride salinity stress using batch culture technique and the genes involved in its biosynthesis pathway employing in silico study. Culture of Botryococcus sp. was grown in Blue-Green 11 (BG11) medium with 16:8 photoperiod of 28 ?mol.s-1.m-2 cool fluorescent light, 25 oC indoor erlenmeyer flask agitated using rotary shaker at 55 rpm. The concentration on 0, 17, 34, and 68 mM sodium chloride was used. The growth data is collected by counting cell number directly from hemacytometer under the microscope. Total chlorophyll and carotenoid content obtained from spectrophotometry analysis. Astaxanthin content of 30, 33, 36, 39, 42, and 45 days old culture measured by High Performance Liquid Chromatography (HPLC) with UV-Vis detector (?: 474nm) and C18 column using methanol:dH2O (95:5) as eluent under 0,4 mL/mins flow rate at 25oC. In silico homology-based gene predicition utilizing B. braunii strain Showa genome was done through KEGG Automatic Annotation Server v.2.1 (KAAS) and Multiple Alignment Fast-Fourier Transform v7 (MAFFT) progressive method. The culture reached its stationary phase after 38 days. Salinity reduced cell number and total chlorophyll content significantly at day 36 while improved total carotenoid and astaxanthin content. The highest total carotenoid and astaxanthin content observed were 4,69 ± 0,19 ?g/mL (34 mM NaCl) at day 45 and 2.71 ± 1.35 ?g/g DCW (68 mM NaC) at day 42, respectively. Salinity stress also accelerated astaxanthin accumulation since day 30 compared to the control group at day 42. In silico study for predicition uncovered 2 genes within astaxanthin biosynthesis pathway, AL1 gene expressing phytoene desaturase and a key crtZ gene expressing ?-carotene hydroxylase. Putative gene of AL1 had TC-Rich repeats inside its promoter sequence which is associated to stress and defense rensponsiveness. These results showed the ability of Botryococcus sp. culture in astaxanthin accumulation and salinity stress could advance astaxanthin biosynthesis.